(untitled) - Hwang, Kai (New York, 1993)
This book deals with advanced computer architecture and parallel programming techniques. The material is suitable for use as a textbook in a one-semester graduate or senior course, offered by Computer Science, Computer Engineering, Electrical Engineering, or Industrial Engineering programs.
Keywords: Computer architecture,Kiến trúc máy tính